Performance-based Outcomes among American Professional Athletes Following Microfracture of the Knee: A Cross-sport Analysis. Issue 7 (21st July 2017) - Schallmo, Michael S.; Singh, Sameer Kumar; Freshman, Ryan; Barth, Kathryn; Mai, Harry; Hsu, Wellington
Objectives: Damage to the articular cartilage of the knee is a common and potentially career-threatening injury among professional athletes. Microfracture is a technique frequently used to treat chondral defects, but the potential benefits of this procedure in the elite athlete population remain unclear. This study sought to assess outcomes after microfracture of the knee among American professional athletes in different sports. Methods: Major League Baseball (MLB), National Basketball Association (NBA), National Football League (NFL), and National Hockey League (NHL) athletes who underwent primary unilateral microfracture of the knee while on the active roster of a professional team and had a definitive date of surgery were identified through a well-established algorithmic approach based on public sources. Demographic information, as well as both pre- and post-surgery regular season player statistics, was compiled for each player. Successful return-to-play (RTP) was defined as returning for at least one professional regular season game after surgery. RTP time was defined as the number of days elapsed between date of surgery and date of first professional game back. Performance scores were calculated for each sport using previously established scoring systems. Players across different sports were compared by adjusting for season and career length differences between sports and by calculating percent change in performance. Results: A total of 131 professional athletes treated with microfracture from 1991 to 2015 met the inclusion criteria. Of these athletes, 103 (78.6%) successfully returned to play (Figure 1). Average time to RTP was 293±146 days. A player's total career games started-to-games played ratio (GS:GP) before surgery was a significant positive independent predictor of RTP ( p =0.039). NBA athletes who returned showed a significant reduction in adjusted games played during their first season post-surgery (61) compared to baseline (100) ( p <0.0001). NBA and MLB athletes demonstrated significantly decreased performance one season after surgery ( p =0.029 and p =0.002, respectively), and NBA athletes also demonstrated significantly decreased performance during post-operative seasons 2-3 ( p =0.024) (Figure 2). BMI, age, career experience (years), games played during index season and total pre-operative career, and GS:GP during index season and total pre-operative career were not found to be predictors of RTP time, career length after surgery (years and games played), or change in performance score. Conclusion: Microfracture of the knee is a serious procedure that has the potential to negatively impact a professional athlete's career. NFL athletes demonstrated the lowest probability of returning after surgery (71.1%), but for those who returned, performance was recoverable to baseline. NBA athletes had a higher-than-average probability of returning to play (82.4%), but those who returned showed a significant decline in performance one season after surgery that was sustained 2-3 seasons post-surgery, and a reduction in games played one season after surgery that was recoverable to baseline by seasons 2-3 post-surgery. Given the small sample size for NHL, microfracture of the knee may be uncommon in these athletes and definitive conclusions cannot be made. The findings of this study demonstrate that outcomes following microfracture vary significantly depending on sport, which is likely due in part to differences in sport-specific tasks. Figure 1: Return-to-play rates following primary unilateral microfracture of the knee for American professional athletes. *MLB athletes returned to play at a significantly higher rate than athletes of all other sports ( p =0.013). **NFL athletes returned to play at a significantly lower rate than athletes of all other sports ( p =0.017). Figure 2: Performance-based outcomes among American professional athletes following primary unilateral knee microfracture surgery. "Denotes significant difference ( p <0.135) compared with pre-surgery season (baseline) for each athlete in cohort. NHL excluded due to small sample size.